Supplementation of Sunflower Oil and Hydrogenated Vegetable Oil and Their Effects on Nutrient Digestibility, Milk Yield and Composition in Crossbred Cows - Jacob, Ani Bency; Balakrishnan, V. (Indian Journal of Animal Nutrition, 2017)
The present study was conducted to compare the supplemental value of sunflower oil and hydrogenated vegetable oil on nutrient digestibility and milk quality including cis-9, trans-11 CLA content in crossbred cows. Ten crossbred cows (BW=248.00 kg; av. milk yield= 6.65 kg/d), 75 days in milk, were randomlydivided into two groups based on their milk yield and days in milk. Hydrogenated vegetable oil and sunflower oil were included in the concentrate mixture of group 1 (HVO) and group 2 (SFO) animals, respectively at a level of 1.5% of total dietary DM. During the 60 days study period, a digestibility trial was conducted towards the end of trial. Nutrient intake and digestibility of nutrients was not affected due to treatments. The milk CLA in SFO group was 2.77 fold higher than that of HVO group. The milk fat and SNF content decreased (P